Honor, Humiliation, and Terror: An Explosive Mix – And How We Can Defuse It With Dignity - Gerson, Janet (In Factis Pax: Journal of Peace Education and Social Justice, 2018)
A Review Essay of Lindner, E. (2017). Honor, Humiliation, and Terror: An Explosive Mix – And How We Can Defuse It With Dignity. Lake Oswego, OR: World Dignity Press, 786 pp., USD 36.00 (paperback), ISBN 978-1-937570-97-2.